Academic podcasting and mobile assisted language learning applications and outcomes - Facer, Betty Rose.; Abdous, Mohammed. (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2011)
Shares innovative and pedagogically effective ways to improve foreign language education by identifying the instructional uses and benefits of academic podcasting technology and MALL in foreign language acquisition. These include instructional uses, students' perceived learning gains, how instructors can use/have used the technology (successes and challenges), study abroad experiences with the technology, pedagogical impact, and economic perspectives on its use.